DEVELOPMENT OF VENTURE CAPITAL AND PRIVATE EQUITY INDUSTRY IN SOUTH AFRICA - Molosi, Bakuedi (2009)
The past decade has seen the development of private equity and venture capital in emerging markets reach unprecedented levels, especially in countries such as China, India and South Africa. Regulatory reforms by the governments in these countries, and change of government in South Africa in particular, has enabled increased foreign direct investment into the country. This development coupled with deliberate policies such as BEE, to encourage ownership and management of enterprise by the previously disadvantaged black population, has enabled the private equity industry in South Africa to be a force to be reckoned with. The industry reached ZAR100 billion mark for the first time in 2008.